How to Learn Like A Pro - Nissila, Phyllis (Open textbook library., 2016)
How to Learn Like a Pro! features the “big six” effective learning/study skills topics: learning styles and preferences, time and materials management, critical thinking and reading, note-taking, memory principles, and test-taking techniques. Each of the six units featuring a total of twenty-three lessons and accompanying exercises (with a dash of humor here and there) were developed with the diverse student body of the community college in mind as well as learners in other educational venues.